Switzerland : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2000)
The Swiss banking system is characterized by a two-tier structure. The first tier is composed of the two large banks and some smaller banks focused on private banking, all of which have a significant international presence. These banks represent, so to speak, the 'international face' of the Swiss banks. They are mostly joint-stock companies or privately owned (unlimited personal liability). The second tier is composed of a varied group of banks, mostly focused on domestic, or even regional, business.